The Type Ia supernova 1999aw: A probable 1999aa-like event in a low-luminosity host galaxy - Strolger, L; Smith, R; Suntzeff, N; Phillips, M; Aldering, G; Nugent, P; Knop, R; Perlmutter, S; Schommer, R; Ho, L; Hamuy, M; Krisciunas, K; et al. (2002)
SN 1999aw was discovered during the first campaign of the Nearby Galaxies Supernova Search project. This luminous, slow-declining [Δm 15(B) = 0.81 ± 0.03] Type Ia supernova was noteworthy in at least two respects. First, it occurred in an extremely low luminosity host galaxy that was not visible in the template images nor in initial subsequent deep imaging. Second, the photometric and spectral properties of this supernova indicate that it very likely was similar to the subclass of Type Ia supernovae whose prototype is SN 1999aa. This paper presents the BVRI and J SHKS light curves of SN 1999aw (through ∼100 days past maximum light), as well as several epochs of optical spectra. From these data, we calculate the bolometric light curve and give estimates of the luminosity at maximum light and the initial 56Ni mass. In addition, we present deep BVI images obtained recently with the Baade 6.5 m telescope at Las Campanas Observatory that reveal the remarkably low-luminosity host galaxy.